2022
DOI: 10.3390/su14031803
|View full text |Cite
|
Sign up to set email alerts
|

What Shapes Activity Preferences? The Role of Tourist Personality, Destination Personality and Destination Image: Evidence from Serbia

Abstract: Understanding activity preferences and their antecedents is essential for creating personalized tourism offers and effective destination marketing, vital components of a sustainable tourism destination. Previous studies have provided insights into tourist behavior and activity choices, but without research on activity preferences and their relationship with perceptions of destinations. The literature still lacks an integrative model exploring the antecedents of activity preferences, including tourist character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 103 publications
1
14
0
Order By: Relevance
“…Moreover, the study results support previous findings (i.e. Kova ci c et al, 2022;Neuburger and Egger, 2021), stating that DI substantially influences the intention to visit. In addition, the findings revealed that familiarity mitigated the negative effects of CFU on DI and travelers' intention to visit when their familiarity with the place was greater than other people's.…”
Section: Key Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the study results support previous findings (i.e. Kova ci c et al, 2022;Neuburger and Egger, 2021), stating that DI substantially influences the intention to visit. In addition, the findings revealed that familiarity mitigated the negative effects of CFU on DI and travelers' intention to visit when their familiarity with the place was greater than other people's.…”
Section: Key Resultssupporting
confidence: 89%
“…According to several studies (i.e. Huang and Hsu, 2009;Kova ci c et al, 2022;Nazir et al, 2021;Neuburger and Egger, 2021;Singh et al, 2022), the DI directly impacts on the intention to visit. Thus, the next hypothesis was established:…”
Section: Coronavirus Fear-uncertainty Perceived Destination Image And...mentioning
confidence: 99%
“…Transforming tourists’ value systems to support sustainable practices is a key concern in the tourism industry (Goh et al , 2017). Encouraging environmentally responsible attitudes and conduct among employees and guests can provide benefits for all stakeholders involved (Kovačić et al , 2022; Miller et al , 2015; Packer et al , 2022). The incorporation of sustainability indicators in destination competitiveness models is significant, as it recognizes the importance of sustainable tourism development (Cucculelli and Goffi, 2016; Ritchie et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this study sheds light on the relevance of national tourism festival celebrations and of building a city's tourism brand image in promoting subsequent inbound tourism at the city level. This has important theoretical implications for destination tourism brand management and impression building and can effectively expand related theories in these fields, such as the tourism destination image theory (Chen et al, 2021;Chen and Li, 2018;Hosany et al, 2006) and the brand management theory of tourist destinations (Ceylan et al, 2021;Jeong and Kim, 2020;Kovačić et al, 2022).…”
Section: Theoretical Implicationsmentioning
confidence: 97%
“…Brand management research has been a hot topic in tourism destination marketing research in recent years and has introduced a lot of new knowledge (Ceylan et al, 2021; Jeong and Kim, 2020; Kovačić et al, 2022). Festivals are the main form of building the cultural and entertainment connotations of modern travel brands within tourism destination marketing (Kozlovska, 2021).…”
Section: Theory Hypothesis Development and Analytical Frameworkmentioning
confidence: 99%